Qualitative cross-sectional study of the perceived causes of depression in South Asian origin women in Toronto - Kwame McKenzie; Samanthika Ekanayake; Farah Ahmad (BMJ Open)
Objective To explore how South Asian origin women in Toronto, Canada, understand and explain the causes of their depression.Design Cross-sectional in-depth qualitative interviews.Setting Outpatient service in Toronto, Ontario.Participants Ten women with symptoms of depression aged between 22 and 65 years of age. Seven were from India, two from Sri Lanka and one from Pakistan. Four were Muslim, three Hindu and three Catholic. Two participants had university degrees, one a high school diploma and seven had completed less than a high school education. Eight were married, one was unmarried and one a widow.Results Three main factors emerged from the participant narratives as the causes of depression: family and relationships, culture and migration and socioeconomic. The majority of the participants identified domestic abuse, marital problems and interpersonal problems in the family as the cause of their depression. Culture and migration and socioeconomic factors were considered contributory. None of our study participants reported spiritual, supernatural or religious factors as causes of depression.Conclusion A personal–social–cultural model emerged as the aetiological paradigm for depression. Given the perceived causation, psycho-social treatment methods may be more acceptable for South Asian origin women.